Cardiovascular computed tomography angiography in newborns and infants with suspected congenital heart disease: Retrospective evaluation of low-dose scan protocols - Klink, Thorsten; Müller, Götz; Weil, Jochen; Dodge-Khatami, Ali; Adam, Gerhard; Bley, Thorsten Alexander (Clinical Imaging, 2012)
Twelve infants (body weight, 3.59±1.36 kg) with congenital heart disease underwent a clinically indicated cardiovascular computed tomography angiography (CTA) study. Retrospectively, we investigated the feasibility and diagnostic capability of different non-electrocardiogram-triggered CTA protocols and assessed radiation doses. Scans were performed on a 256-multislice CT (MSCT) scanner with the vendor-preset helical protocol at 120 kV for babies, with axial single-shoot scans at 120 kV and 80 kV. The 80-kV protocol led to significantly reduced mean effective doses of 0.29±0.08 mSv (P=.017) and renders diagnostic image quality. All major cardiovascular defects were detected on MSCT, and all images were of diagnostic quality. © 2012 Elsevier Inc.
CRIS-Team Scopus Importer:2024-12-04
Keywords: Computed tomography angiography (CTA); Congenital heart disease; Low radiation dose; Newborns; Pediatrics